2014
DOI: 10.13171/mjc.3.4.2014.20.07.14
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study by UV Spectrophotometry of Carzol degradation in aqueous medium

Abstract: This paper deals with the kinetic hydrolysis in aqueous media of Carzol or (E) 3-dimethylamino- methyleneaminophenyl-N-methylcarbamate hydrochloride. The Carzol is a bifunctional compound which belongs to the chemical families formamidine and carbamate. This work is carried out by UV Spectrophotometry. The successive determination of 3-aminophenyl-N-methylcarbamate and 3-aminophenol, as the mainproducts of the formamidine and the carbamate groups of Carzol hydrolysis gives evidence for the significant reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The positive value of the activation entropy is in agreement with the mechanism E1cB. Comparable values were obtained for the hydrolysis reaction of a series of N ‐methylcarbamates studied in our laboratory: carbaryl , carbofuran , methiocarb , bendiorab , zectran , aminocarb , landrin , ethiofencarb , carzol , and isoprocarb .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The positive value of the activation entropy is in agreement with the mechanism E1cB. Comparable values were obtained for the hydrolysis reaction of a series of N ‐methylcarbamates studied in our laboratory: carbaryl , carbofuran , methiocarb , bendiorab , zectran , aminocarb , landrin , ethiofencarb , carzol , and isoprocarb .…”
Section: Resultssupporting
confidence: 81%
“…The corresponding mechanism involves either an addition of OH − into the carbonyl with a further elimination of the RO − leaving group or an abstraction of the hydrogen of the methylcarbamate moiety again evolving with the elimination of the RO − group. Consequently, we have undertaken in our laboratory a study of the determination of both the kinetic and mechanistic aspects of the hydrolysis reaction of carbaryl , carbofuran , methiocarb , bendiocarb , zectran , aminocarb , landrin , ethiofencarb , carzol , isoprocarb , and pirimicarb . We showed that hydrolysis of PNMCs exhibited pseudo–first‐order kinetics with respect to substrate in aqueous media.…”
Section: Introductionmentioning
confidence: 99%